Development of Physical Fitness Test Measurement Application for Teacher Working Group and Subject Teacher Deliberation Physical Education in Tanjung Redeb District, Berau Regency - Muhammad Rifqi Aidiansyah; Rumini; Donny Wira Yudha Kusuma (Universitas Negeri Semarang, 2025)
This research aims to develop an android-based physical fitness test measurement application to facilitate PE teachers in implementing and managing the results of students' physical fitness tests effectively and efficiently in the Elementary School Teacher Working Group and the Subject Teacher Meeting of Junior High School Tanjung Redeb District, Berau Regency. The research method uses the Research and Development (R&D) Borg and Gall model which is modified into three stages including preliminary study, product development, and experiment with physical education teacher research subjects and selected students. The research instrument was in the form of an expert validation questionnaire using a likert scale with a value range of 1-4, while the data analysis used descriptive statistics and a T-test test to measure the effectiveness of implementation. The results of expert validation showed a very high feasibility rate with a percentage of 91%-100%, small group trials obtained 82%, and large group trials reached 87% for the elementary level and 88% for the junior high school level. The implementation of the application through pretest and posttest resulted in an increase in the physical fitness category of students from less to less at the elementary level, and from less to moderate at the junior high school level in a span of two weeks. The conclusion of this study shows that the TESPEN TKJI application is feasible and effective in increasing teachers' understanding of physical fitness tests, facilitating the assessment process through automating calculations and structured databases, and providing a positive influence on improving students' physical fitness through continuous monitoring of development.